PENGARUH KUALITAS PELAYANAN, HARGA DAN CITRA MEREK TERHADAP KEPUASAN MAHASISWA - Titim Nurlia (POLITEKNIK LP3I JAKARTA, 2019)
Highly competition requires university to be more sensitive to the interest students as one of stakeholders. Polytechnic LP3I Jakarta Campus Cimone has many competitors amid the dynamics of increasingly fierce competition of higher education. This research aims to analyze the effect of Service quality, Price and Brand Image of Students Satisfaction. A theory used in research is based on opinion from Andriyani, Suwandi Mananeke & Taroreh, Fatriansyah. There is an effect between Service Quality, Price and Brand Image to Customer Satisfaction. This research use a quantitative method by distributing a questionnaire. The amount of population are 408 students and the sample is 80 people by Slovin formulas. Based on research result using linear regression analysis multiple SPSS version 20 indicated that: The independent variable Service Quality, Price and Brand Image jointly tested by F test proved positive and significant influence on the Student Satisfaction and the magnitude of the effect seen from the coefficient of determination (R2) was 41,8 %. To test the hypothesis of the use F test and t test. While price do not have effect significant influence on students satisfaction. Keywords: service quality, price, brand image, student’s satisfaction